Satellite Based Internet Education Delivery and E-Learning Objects Evaluation: SOI Asia and Codewitz Perspective - Islam, M. S.; Alam, J. B.; Kabir, S. M. L. (INTI International University, 2007)
Development of Internet based distance education facilities and e-learning objects development commensurate with the capacity building and modernization process of Bangladesh University of Engineering and Technology (BUET) and is congruent with the long term objective of the institution regarding facilitation of continuing education satisfying the temporal and spatial constraints. To fulfill the objectives, BUET has established the satellite based School on the Internet (SOI) project and has become active partner in the global e-learning object development program through Codewitz project. In this paper we present, (i) the technology used to deliver the real time lectures through SOI, (ii) the content and quality assessment of the delivered lecture by the participants and its overall impact in the human resource development in BUET, (iii) the development of e-learning objects for different programming languages, and (iv) the quality evaluation of the developed objects and interest from other stakeholders of the Codewitz project.